Pathomorphological Damage to the Lung in Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
During a pandemic, SARS-CoV-2 has been found to primarily affect the upper respiratory tract and lungs. Due to increased replication of the virus with the epithelium of the respiratory tract, acute respiratory distress syndrome develops; due to viremia, impaired immune system, hypoxia of tissue structures, clinical worsening of the patient’s condition is noted within 2 weeks. In this work, 8 cases of autopsy material were taken to study pathomorphological changes in the lungs. It was found that under the influence of the virus, damage was observed to the integumentary epithelium of the bronchi and alveoli, tissue structures of the vascular wall and interstitial tissue, due to which the development of destruction in the form of atelectasis, distelectasis and the development of distress syndrome was noted. The peculiarity of damage to the lung tissue, vascular walls and interstitium manifested itself in the form of proliferation of connective tissue cells with the development of fibroplastic alveolitis.